PERLINDUNGAN HUKUM PIDANA LINGKUNGAN TERHADAP KEGIATAN PERUSAHAAN PERTAMBANGAN DALAM PRNANGGULANGAN DAMPAK LINGKUNGAN - Rasjuddin Rasjuddin (Unissula, 2020)
The purpose of this study is to determine the extent of environmental criminal law policies on mining management activities, to determine how environmental management is implemented in mining activities, and to determine the inhibiting factors for environmental criminal law policies. This research method uses an empirical juridical approach. The findings in this study are mining crime focuses on licensing and does not differentiate between criminal offenses and offenses. Between individual legal subjects and business entities (corporations), the criminal sanctions are regulated in the same Article. only for corporations or legal entities, the fine is up to 1/3 (one-third) of the maximum penalty imposed. The cumulative punishment is the imposition of two sentences at once, in the form of imprisonment and fines. Meanwhile, the alternative is that the judge chooses one sentence of imprisonment or imprisonment. The formulation of the criminal threat is categorized as quite high and heavy, but the application for the criminal offender, none of the perpetrators can be arrested and processed by the court.